2020
DOI: 10.1111/dmcn.14630
|View full text |Cite
|
Sign up to set email alerts
|

Hand–arm bimanual intensive therapy and daily functioning of children with bilateral cerebral palsy: a randomized controlled trial

Abstract: Aim To examine the efficacy of Hand–Arm Bimanual Intensive Therapy (HABIT) on daily functioning, unimanual dexterity, and bimanual performance of children with bilateral cerebral palsy (CP) compared with customary care. Method Forty‐one children with bilateral CP, aged 4 to 16 years, classified in levels I to III of the Manual Ability Classification System, were randomly assigned to HABIT (90h) (n=21) or to customary care (4.5h) (n=20). Participants’ daily functioning (Pediatric Evaluation of Disability Invent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 29 publications
1
14
0
2
Order By: Relevance
“…Although the BBT has been widely used to measure the effectiveness of neurorehabilitation programs in children with UCP 7 , 14 , 16 , 17 , only its test–retest reliability and responsiveness have been investigated 18 . The measurement error such as minimal detectable change (MDC, defined as the minimal amount of change that surpasses random measurement error) 19 , the construct validity, and the interpretability such as the minimal clinically important difference (MCID, defined as the minimal change score that is clinically meaningful for the respondents) 20 of the BBT have not been investigated yet in children with UCP.…”
Section: Introductionmentioning
confidence: 99%
“…Although the BBT has been widely used to measure the effectiveness of neurorehabilitation programs in children with UCP 7 , 14 , 16 , 17 , only its test–retest reliability and responsiveness have been investigated 18 . The measurement error such as minimal detectable change (MDC, defined as the minimal amount of change that surpasses random measurement error) 19 , the construct validity, and the interpretability such as the minimal clinically important difference (MCID, defined as the minimal change score that is clinically meaningful for the respondents) 20 of the BBT have not been investigated yet in children with UCP.…”
Section: Introductionmentioning
confidence: 99%
“…The satisfaction scores of the COPM increased significantly immediately after BIMT, though a slight decrease was observed at six months follow-up. A recent report by Figueiredo et al [ 43 ] showed similar results in a group of children with bilateral CP participating in an intensive 90 h bimanual training program called HABIT. The group that performed the program exhibited greater improvements in performance and satisfaction with the performance of functional goals and functional skills than children who maintained their customary care routines and are following the results found by Bleyenheuft et al [ 44 ].…”
Section: Discussionmentioning
confidence: 55%
“…The full texts of the remaining 174 papers were screened, revealing that 25 articles did not compare the protocol of interest with another upper limb manual training, 14 were study protocols, 15 were not published yet, 5 included pretreatment with botulinum toxin, 11 were dose-effect studies, 19 had the duplicated study group, 23 were not peer-reviewed articles, 19 were not randomized controlled trials, 3 included participants who did not have cerebral palsy, 10 with data unassessable, 5 did not illustrate functional outcomes, and 3 used combination therapy. Finally, 22 articles 7,11,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] were selected for this network meta-analysis (Figure 1).…”
Section: Resultsmentioning
confidence: 99%